Solving Nonlinear Two Point Boundary Value Problems Using Exponential Finite Difference Method - Pramod K. Pandey (Boletim da Sociedade Paranaense de Matemática, 2016)
In this article, we present exponential finite difference scheme for solving nonlinear two point boundary value problems with Dirichlet's boundary conditions . The local truncation error and under appropriate condition we have discussed the convergence of the proposed method. Numerical experiments demonstrate the use and computational efficiency of the method. Numerical results show that this method is at least fourth order accurate, which is good agreement with the theoretically established order of the method.